O-B02 Robotic versus Laparoscopic Roux-en-Y Gastric Bypass: A comparison of short-term outcomes and weight loss. (16th December 2021) - Hamdan, Mohammed; Messina, Gianfranco; Duck, Eleanor; Shenoy, Aniruddh; Gill, Gurpreet Singh; Jones, Gregory; Sampson, Marianne; Ramus, James
Abstract: Background: The benefits of robotic over laparoscopic surgery for Roux-en-Y gastric bypass (RYGB) are debatable, with current evidence suggesting no significant differences in short-term outcomes. This study compares short-term outcomes and excess weight loss (EWL) % difference between these two techniques. Methods: A retrospective study of patients undergoing RYGB between January 2016 and November 2020 at a single centre. Demographic, peri-operative and EWL% data were analysed. Results: 424 RYGB procedures were performed by three surgeons including 77 robotic (RRYGB) and 347 laparoscopic (LRYGB) operations. The first 8 RRYGB were excluded being early in the learning curve and the operative technique was modified afterwards. There were no statistically significant demographic differences. The median operative time was 179 (151 – 195) and 149 (123 -171) minutes in the RRYGB and LRYGB groups respectively (P < 0.001). There were no statistically significant differences between both groups in complications, length of stay, 30-day readmission and EWL% at 6 and 12 months. The EWL% at 2 years was 88.5 (+/-19.1) and 66.6 (+/-29.8) in the RRYGB and LRYGB groups respectively (P = 0.003). Conclusions: RRYGB increases the operative time with no significant short-term outcome differences. The EWL% was higher at 2 years, probably due to a narrower hand-sewn gastro-jejunal anastomosis.